PENGARUH KOMUNIKASI DAN KEPUASAN TERHADAP KEPERCAYAAN DAN KOMITMEN UNTUK MELAKUKAN HUBUNGAN PEMASARAN JANGKA PANJANG - MULYANA MULYANA; PUSPITA SARI (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2009)
This research is study the process which influence the relationship development (marketing)based on commitment. The excellence of continual competitive from company can do with thelong-range cooperation relationship. In this cooperation relationship, the role of commitmentis very importance. Research in Juwana indicate that trust is the primary factor in courseof development of long-range marketing cooperation commitment. Trust is influenced bysatisfaction and communications. Type of research is explanatory research, population inthis research is all of cutomer. Technique used in this research is census so all of populationwill be sampel. Technic analysis used in this research is equation model of structural byPartial Least Square ( PLS). Communications and satisfaction have an influence to trust thensatisfaction and communications also have an influence on directly to commitment. Trust inthis case also have an influence to commitment.Keywords : Communication, Satisfaction, Trust, Commitment